Effect of consuming lemongrass (Cymbopogon citratus) on shortening the postpartum period - Meidawati, Gusti Sophia; Rahmawati, Dwi; Noval; Mahdiyah, Dede (Health Sciences International Journal, 2024)
Background: Complementary care in some midwifery communities has become important to midwifery practice. One of the reasons why complementary midwifery care is currently widely used is the desire to avoid the side effects of drugs. Based on the birth register at Independent Practice of Midwife Darmawati from September to December 2023, the average number of births was 25 patients a month, with postpartum visit data recorded as 89% of postpartum mothers consuming lemongrass decoction (Cymbopogon citratus) during the postpartum period. Lemongrass is a natural resource proven to speed up the healing process. Lemongrass is rich in potassium, which stimulates blood circulation, improves blood flow, and helps increase endurance. Objective: The aim is to determine the effect of consuming lemongrass decoction on shortening the postpartum period. Method: This research method uses a quasi-experimental research design with a treatment group and a control group design. The population of this study was all postpartum mothers recorded in the IPM Darmawati birth register from September 2023 to January 2024. This research used a tool in the form of an observation sheet which was filled out by respondents in the treatment group every time they drank lemongrass decoction according to the manual for making lemongrass decoction and how to consume it. Results: In the intervention group 25% had the postpartum period in the normal category, and 75% in the fast category, while in the control group 100% were in the normal. The Wilcoxon test results show a significant difference between the treatment and control group with a p-value of 0.042. Conclusion: Consuming lemongrass decoction significantly shortened the postpartum period.